ANALISIS PERKEMBANGAN EMOSIONAL SISWA SEKOLAH DASAR: STUDI OBSERVASI DI KELAS III SD NEGERI 13 KURANJI PADANG - Mitha Andriani; Fiola Wulandari; Naya Febriani Putri; Naysha Az-Zahra Fisal; Dina Amsari (STKIP Subang, 2026)
Emotional development is a fundamental aspect of the growth process of elementary school students. Although studies on children's emotional intelligence have been conducted extensively, research that directly integrates field observation data, questionnaires, and interviews in the context of lower elementary school classes in Indonesia remains limited. This study aims to analyze emotional development patterns of grade III elementary school students, encompassing emotional responses to various school situations, emotion regulation abilities, peer influence, and the teacher's role in guiding students' emotional development. A descriptive qualitative approach supported by simple quantitative data was employed. Data were collected through direct observation, emotion questionnaires (15 respondents), in-depth interviews with two students and the homeroom teacher, and documentation. Observations were conducted on November 24, 2025, in Class III C of SD Negeri 13 Kuranji, Padang. Results indicate that most students responded to responsibility with pride (60%), demonstrated adequate emotional control in mild conflict situations (80% chose patience), and predominantly expressed positive emotions in cooperative learning contexts (86.7%). However, social situations such as peer exclusion and teacher punishment evoked negative emotions of sadness and fear. The homeroom teacher played a significant role in moderating student emotions through personal approaches and avoiding inter-student comparisons. These findings imply the importance of emotionally responsive teaching strategies and consistent positive reinforcement as part of elementary teachers' pedagogical practice.